Kualitas Kompos dari Kombinasi Eceng Gondok (Eichornia crassipes Mart. Solm) dan Pupuk Kandang Sapi dengan Inokulan Trichoderma harzianum L. - Masnur Turnip, Devi Ayu Wulandari, Riza Linda (Jurnal Protobiont, 2016)
Water Hyacinth (E. crassipes Mart. Solm) and cow manure can be used as organic fertilizer because they are organic materials which contain C, N, P, and K needed by plants. The composting process of E. crassipes and cow manure cannot be directly used as compost as they need a decomposer to accelerate thedecomposition of composting by adding T. harzianum. This research aims to find out the quality of compost from a combination of water hyacinth (E. crassipes) and cow manure with inoculant T. harzianum. The study was conducted for three months from March to May 2015. The method used was theCompletely Randomized Design (CRD) with Replacemant Series method consisting of five stage treatments which were repeated 3 times. The results indicated that the organic C content ranged between 31.29% and 35.42%, nitrogen content between 1.57% and 2.28%, the ratio of C / N ranged between 14.20 and 19.20, P2O5 ranged between 0.47% and 0.72%, K2O between 2.27% and 5, 57%, water content between 14.97% and 29.16%, pH between 6.4 and 6.8, the temperature between 270C and 280C, and humidity between 54.6% and 58.3%.